2022
DOI: 10.3390/jcm11041009
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability in Single-Leg Quiet Stance in Highly Trained Athletes: Sex and Sport Differences

Abstract: This study aimed to determine if there is a difference in postural stability in highly trained adolescents and young adult athletes regarding sex and sport. The participants were young athletes (n = 464) from seven different sports. We considered the center of pressure (CoP) velocity (total, anterior–posterior (AP) and medial–lateral (ML)), CoP amplitude (AP and ML), and CoP frequency (AP and ML), as assessed by single-leg quiet stance test. Significant interactions were found between sex and sport for all CoP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…For the Single Leg Balance test, the MVcop values obtained with PLATES under laboratory conditions were 39.1 ± 4.3 and 40.7 ± 7.4 mm/s with eyes open and 72.7 ± 10 and 78.4 ± 9.3 mm/s with eyes closed for the left and right leg, respectively. These MVcop values are similar to previous study results [ 31 ]. Concerning the results of MVcop with the PLATES under field conditions, we obtained 38.3 ± 5.7 and 41.6 ± 6.3 mm/s with eyes open and 76.3 ± 9.3 and 82.2 ± 12.3 mm/s with eyes closed for the left and right leg, respectively.…”
Section: Resultssupporting
confidence: 93%
“…For the Single Leg Balance test, the MVcop values obtained with PLATES under laboratory conditions were 39.1 ± 4.3 and 40.7 ± 7.4 mm/s with eyes open and 72.7 ± 10 and 78.4 ± 9.3 mm/s with eyes closed for the left and right leg, respectively. These MVcop values are similar to previous study results [ 31 ]. Concerning the results of MVcop with the PLATES under field conditions, we obtained 38.3 ± 5.7 and 41.6 ± 6.3 mm/s with eyes open and 76.3 ± 9.3 and 82.2 ± 12.3 mm/s with eyes closed for the left and right leg, respectively.…”
Section: Resultssupporting
confidence: 93%
“…A comparison of static balance results (single-leg stance position) for young athletes in Slovenia identifies higher values of dancers compared to other sports, and girls perform significantly better than boys [69]. The evaluation of Danish athletes (14-24 years old) on the One-leg standing test identified superior values of static balance for basketball players (positive associations with seniority in sports), but did not indicate significant differences between genders or age stages [70].…”
Section: Comparison Of Results With Similar Studies On Balance Values...mentioning
confidence: 89%
“…On the other hand, Hahn et al reported a positive correlation between the SLS-EO and SLS-EC test results and time spent in basketball training, while this correlation was negative for swimming [38]. Various studies have shown that the type of sport practiced can influence postural stability [37,39]. For example, Trajković et al found among athletes from seven different sports that dancers demonstrated significantly better stability on one leg compared to others [39].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that the type of sport practiced can influence postural stability [37,39]. For example, Trajković et al found among athletes from seven different sports that dancers demonstrated significantly better stability on one leg compared to others [39].…”
Section: Discussionmentioning
confidence: 99%